Estrogen Mediates an Atherosclerotic-Protective Action via Estrogen Receptor Alpha/SREBP-1 Signaling - Xie, Fei; Li, Xiandong; Xu, Yue; Cheng, Dongliang; Xia, Xianru; Lv, Xi; Yuan, Guolin; Peng, Chunyan (Frontiers in Cardiovascular Medicine, 2022)
Menopause is associated with dyslipidemia and an increased risk of cardiovascular disease, the underlying mechanism of dyslipidemia is attributed to an insufficiency of estrogen. In this study, we find that estrogen mediates an atherosclerotic-protective action via estrogen receptor alpha/SREBP-1 signaling. Increased lipid accumulation and low-density lipoprotein (LDL)-uptake in HepG2 cells and THP-1 macrophages were induced by treatment of mixed hyperlipidemic serum from postmenopausal women; 17β-estradiol [estrogen (E2)] (10 nM) administration significantly improved hyperlipidemic profiles, relieved fatty-liver damage and attenuated the plaque area in the heart chamber of high-fat diet (HFD)-fed ovariectomized (OVX) ApoE–/– mice. Expression of sterol regulatory element-binding protein (SREBP)-1 mRNA of circulating leukocytes in postmenopausal women was strongly correlated to the serum E2 level. Exploration of data from the Gene Expression Profiling Interactive Analysis (GEPIA) database revealed that expression of SREBP-1 protein correlated to expression of estrogen receptor (ESR)α protein in the liver, blood and in normal tissue. Genetic overexpression/inhibition of ESRα resulted in increased/decreased SREBP-1 expression as well as attenuated/deteriorated lipid deposition in vitro. An inhibitor of the protein kinase B/mammalian target of rapamycin (AKT/mTOR) pathway, AZD8055, abolished ESRα-induced SREBP-1 expression in HepG2 cells. Moreover, E2 and statin co-treatment significantly reduced lipid accumulation in vitro and hindered the progression of atherosclerosis and fatty-liver damage in OVX ApoE–/– mice. Collectively, our results suggest that estrogen could exerted its atherosclerotic-protective action via ESRα/SREBP-1 signaling. E2 might enhance the cellular sensitivity of statins and could be used as a novel therapeutic strategy against atherosclerotic disorders in postmenopausal women.